2018
DOI: 10.1177/1369433218804928
|View full text |Cite
|
Sign up to set email alerts
|

Imperfection sensitivity in cylindrical shells under uniform bending

Abstract: Efforts are ongoing to characterise a comprehensive resistance function for cylindrical shells under uniform bending, a ubiquitous structural system that finds application in load-bearing circular hollow sections, tubes, piles, pipelines, wind turbine support towers, chimneys and silos. A recent computational study by Rotter et al. (2014) demonstrated that nonlinear buckling of perfect elastic cylinders under bending is governed by four length-dependent domains-'short', 'medium', 'transitional' and 'long'-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…A similar trend is known to exist in the bifurcation buckling of very short single cylinders and, is related to the effect of boundary conditions on development of membrane stresses [19]. In the vicinity of boundaries, larger moments are required to cause a finite segment of the shell to reach its critical membrane stress [16,21].…”
Section: Effect Of Length On Linear Critical Buckling Moment Of Pips supporting
confidence: 55%
See 4 more Smart Citations
“…A similar trend is known to exist in the bifurcation buckling of very short single cylinders and, is related to the effect of boundary conditions on development of membrane stresses [19]. In the vicinity of boundaries, larger moments are required to cause a finite segment of the shell to reach its critical membrane stress [16,21].…”
Section: Effect Of Length On Linear Critical Buckling Moment Of Pips supporting
confidence: 55%
“…Previous studies [16,19] have shown that the linear elastic buckling moments and shape and number of the wrinkles at the onset of buckling of the tubes, are significantly influenced by their lengths. Using Eigen-buckling analysis in ANSYS [33], and assuming isotropic linear material definition with parameters shown in Table 2 In very short PIP, where the length of the system is of the order of the bending half wave length of the outer pipe, the critical buckling moment is significantly higher than the classical buckling moment of the system proposed in Eq.…”
Section: Effect Of Length On Linear Critical Buckling Moment Of Pips mentioning
confidence: 97%
See 3 more Smart Citations